2015
DOI: 10.1097/mou.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor spasm as a cause of voiding dysfunction

Abstract: Pelvic floor spasm and associated voiding problems are heterogeneous in their pathogenesis and are therefore often underrecognized and undertreated; it is therefore essential that a therapeutic strategy needs to be personalized to the individual patient's requirements. Therefore, careful evaluation and assessment of individuals using a multidisciplinary team approach including a trained physical therapist/nurse clinician is essential in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The assessing clinician must therefore be aware of FUS as a cause of LUTS in females, to minimize the potential for misdiagnosis. Voiding dysfunction due to neuromuscular dysfunction of the pelvic floor and external urethral sphincter would appear to be relatively common (9), though accurate characterization of the cause of voiding dysfunction in women is lacking.…”
Section: Female Urethral Stricture (Fus)mentioning
confidence: 99%
“…The assessing clinician must therefore be aware of FUS as a cause of LUTS in females, to minimize the potential for misdiagnosis. Voiding dysfunction due to neuromuscular dysfunction of the pelvic floor and external urethral sphincter would appear to be relatively common (9), though accurate characterization of the cause of voiding dysfunction in women is lacking.…”
Section: Female Urethral Stricture (Fus)mentioning
confidence: 99%
“…In a recent review, Kuo et al. addressed the importance of pelvic floor spasm in the origin of voiding dysfunction in females (Kuo et al, 2015). Moreover, in normal conditions there is an important bladder-to-urethra reflex mediated by sympathetic efferent pathways.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Our results confirm prior published literature reporting a possible association between PFMP and lower urinary tract symptoms . We found that patients who report symptoms typically attributed to a UTI do not have evidence of a UTI on a catheterized urine specimen.…”
Section: Discussionmentioning
confidence: 99%